Aprendizagem significativa e a prática docente do professor de língua portuguesa - Espens, Silvana (2022)
The presented text refers to the dissertation developed together with the research line of Educative and Language Process at the Post-Graduation in Education of the University of Passo Fundo. The investigation starts from the importance that the Portuguese language teacher develops didactic actions aimed at favoring the students' meaningful learning. The identified question is linked to the results not Always satisfactory that teachers and the largescale tests point in relation to this curricular content. Within the suggested possibilities is the one that says that teaching strategies aiming to promote a meaningful learning are not being appreciated by teachers in their educational activity. Therefore, the following question is taking as central issue of the study: how often Portuguese teachers use in their teaching favor inspiring situations of a meaningful learning? The objective is in to analyze the frequency which teaching strategies associated to meaningful learning are used by Portuguese teachers of Elementary school – Final Years. For the development of the research, a questionnaire was applied to a group of teachers who teach Portuguese language classes in Elementary School – Final Years. The questionnaire refers to a translation and adaptation of the one proposed by Hernández Jacquez and Ríos Zavala (2017) which, in turn, is referenced in the Ballester Method and in the Theory of Meaningful Learning by David Ausubel. The questionnaire used in the study involves the context of the didactic action of Portuguese Language teachers and its initial application was carried out in the form of a pilot study, with a group of five teachers. This study pointed out the necessary adjustments and adaptations for the application of the definitive study that took place with a universe of 32 teachers from the municipal public network of Passo Fundo, RS. The teachers invited to participate act in the curricular component of Portuguese at the Elementary School – Final Years. The data analysis producted with the application of the questionnaire, occurred by six categories given a priori by the six variations listed by Ballester as members of a teaching directed to promote the meaningful learning. The results indicate that the examined teachers presented high frequency of using in five of the six categories/variables (Open Work; Motivation; Environment; Creativity; Curricular Adjustments) and, a low frequency using Conceptual Maps. Such results do not support the initial hypothesis of the study, but opens possibilities for new investigations in which is considered a more effective analysis of the practice of teachers through direct observations and interview with them.